Wetting and interfacial reactions: Experimental study of the Sb-Sn-X (X = Cu, Ni) systems - Novaković R.M.; Delsante S.; Borzone G. (Journal of Mining and Metallurgy. Section B: Metallurgy)
Experimental studies of the Cu-Sb-Sn and Ni-Sb-Sn systems have been carried out by the wetting tests, followed by the analysis of the microstructural evolution occurring at the interface between the liquid alloy and solid substrate. The wetting experiments on the Sb30Sn70 / (Cu, Ni) and Sb38.4Sn61.6 / (Cu, Ni) systems have been performed by using a sessile drop apparatus. The wetting behaviour of the two alloys in contact with Cu-substrate differs from that observed in the case of Ni-substrate. The Sb-Sn alloy / substrate interface was characterised by SEM-EDS analyses. For each system, the solidliquid interactions and the phases formed at the interface were studied with the help of the corresponding phase diagrams.